CHEMICAL COMPOSITION AND SALT LOAD IN RAINWATER OF MOSUL CITY-NINEVEH GOVERNORATE - Amer Abdul-Kareem; M.T. S. Khalil; K.E. AL-Hadidi (Mesopotamia Journal of Agriculture)
The present study reports the chemical composition and atmospheric salt load rainwater of Mosul city/ Nineveh Governorate / Iraq. The sampling were done from October 2012 to March 2013. Twenty six samples were collected and analyzed for pH, ion concentration (Ca++, Mg++, K+, Na+, CI-, HCO3-, SO4--) and electrical conductivity. Total rainwater was 338.55mm. The results show that the volume weighted mean (VWM) pH and electrical conductivity in the rainwater were 6.83 and 114.22µS.cm-1 respectively. Cation and anion concentration took the  following order : Ca++ ˃ Mg++ ˃ Na+ ˃ K+ and HCO3- ˃ CI- ˃ SO4=.  HCO3- and Ca++ contributed 65.3% of the total ions in the rainwater. Equivalents ratios for different ionic components to sodium, revealed higher values in rainwater than that of seawater. This indicates the dominance of non-marine in studied samples. Analyses  revealed  that loads delivered from the fallen precipitation in the urban city of Mosul was about 0.1167kg cl-/m3 of chloride in rainwater  which equal numerically to 395kg  NaCI. h-1 of land.